FAKTOR-FAKTOR PENYEBAB KESULITAN BELAJAR SISWA DALAM MENGIKUTI PELAKSANAAN BELAJAR TUNTAS - Minarti Minarti; Berchah Pitoewas; Hermi Yanzi (Jurnal Kultur Demokrasi, 2015)
The focus of this research is to analyze and explaine the factors causing student learning difficulties in following the implementation of Mastery Learning. This research is using descriptive qualitative methods with a population of 155 respondents. Based on the results of the research, it shows that: (1) Indicators of motivation as many as 45,16% of respondents is categorized as a moderate motivation. (2) Indicators of teachers as many as 48,39% of respondents is categorized as a strong influential. (3) Indicators of facilities and infrastructure as many as 70,97% of respondents is categorized as a less influence. (4) Indicators of learning speed as much as 58,06% of respondents is categorized as a moderate learning speed. (5) Indicators of time as much as 48,39% of respondent is categorized as a very influential. So it can be concluded that the implementation of completed learning still need to be optimized do that the difficulty in learning of the students can be handled.Fokus penelitian ini adalah untuk mengalisis dan menjelaskan faktor-faktor penyebab kesulitan belajar siswa dalam mengikuti pelaksanaan belajar tuntas. Penelitian ini menggunakan metode deskriptif kualitatif dengan jumlah populasi 155 responden. Berdasarkan hasil penelitian menunjukan bahwa: (1) indikator motivasi sebanyak 45,16% responden masuk kategori motivasi sedang. (2) Indikator guru sebanyak 48,39% responden masuk kategori sangat berpengaruh. (3) Indikator sarana dan prasarana sebanyak 70,97% responden masuk kategori kurang berpengaruh. (4) Indikator kecepatan belajar sebanyak 58,06% responden masuk kategori kecepatan belajar sedang. (5) Indikator waktu sebanyak 48,39% reponden masuk kategori sangat berpengaruh. Jadi dapat disimpulkan bahwa penerapan belajar tuntas masih perlu dimaksimalkan agar kesulitan belajar siswa dapat teratasi.Kata kunci: belajar tuntas, kesulitan belajar, siswa.